Leader humility dan work engagement pada karyawan perbankan syariah: Peran power distance orientation - Hanuna Shafariah; Abdul Gofur (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
This study bridges the theoretical debate regarding the effectiveness of humble leaders in Asian cultures, especially employees in Islamic banks in Indonesia. A total of 162 employees in several Islamic banks were involved in the study. The first results show that humble leaders have a dual effect (u-shaped relationship), which can positively impact work engagement but can also have a negative effect if applied too much. Furthermore, using moderation regression, power distance orientation has an important role and can reduce the effectiveness of humble leaders on employee engagement.